If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3x + 2 = -8x + -1i Reorder the terms: 2 + 7x + -3x = -8x + -1i Combine like terms: 7x + -3x = 4x 2 + 4x = -8x + -1i Reorder the terms: 2 + 4x = -1i + -8x Solving 2 + 4x = -1i + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 2 + 4x + 8x = -1i + -8x + 8x Combine like terms: 4x + 8x = 12x 2 + 12x = -1i + -8x + 8x Combine like terms: -8x + 8x = 0 2 + 12x = -1i + 0 2 + 12x = -1i Add '-2' to each side of the equation. 2 + -2 + 12x = -2 + -1i Combine like terms: 2 + -2 = 0 0 + 12x = -2 + -1i 12x = -2 + -1i Divide each side by '12'. x = -0.1666666667 + -0.08333333333i Simplifying x = -0.1666666667 + -0.08333333333i
| -(6y+7z-8x)= | | (10-t)(10+t)=0 | | 6x+2(5x+12)=25-2(1-8x) | | 16-2t=3/2t | | X+.20x+35=89 | | 25.20x+20=71 | | 2n+6n=72 | | 25.20x+0.20=71 | | 7x-21=7(x-4)+7 | | 42x=-64 | | a^2b-b^3= | | (9k-2)2=0 | | 17x-7=0 | | (21y-1)+(4x+23)+(9x-38)=180 | | 2y^3/4h^2(2y^1/3h^-4)^6 | | 4x-10=x-1 | | -(3z+2x)= | | 85-3=49 | | a^2-12a+26=-6 | | -7=13+.4b | | (10-t)(10+r)=0 | | 8/3c-2=2/3c=12 | | -28m-12=88 | | 0.09xX=61.67 | | P(w)=5w^2-9w+9 | | 3.3q-5.7-3.4q=-2.1q-5.2 | | 7x+(x+20)= | | x-8-12=5 | | (4-s)(4-s)=0 | | 5m^2+28m+32=0 | | x+12-18=26 | | 5m^2+28+32=0 |